The making of foreign policy in Russia under Yeltsin - Suzanne Crow. (RFE/RL Research Institute, 1993)
Includes bibliographical references. "RFE/RL Studies are concise analyses of important issues and developments in Russia, Transcaucasia and Central Asia, and Central and Eastern Europe. They are prepared by scholars and researchers at the RFE/RL Research Institute in Munich."